Bibliometric analysis on hydrogen and ammonia: a comparative evaluation for achieving IMO's decarbonization targets - Elcicek, H. (SPRINGER, 2024)
In the last decade, shipping emissions have emerged as a prominent contributor to climate change. In 2018, the IMO introduced a strategy encompassing short-, mid-, and long-term actions to address this issue. Future studies should prioritize clean alternative fuels to ensure adequate implementation supports the strategy's long-term objectives, effectively reducing shipping emissions. This study aimed to present a comprehensive evaluation of the carbon-neutral alternative fuels hydrogen and ammonia for reducing CO2 emissions from ships. Moreover, a bibliometric analysis was conducted using data obtained from the SCOPUS database to comprehend relevant topics, enhance collaboration networks, and determine research focal points. A total of 920 journal articles published from 2000 to December 2022 were retrieved and evaluated. The findings revealed that after the 2015 Paris Agreement and the IMO vision of 2018, the number of publications increased exponentially, leading to a continuous increase in the total number of publications to date. The searches conducted in the Scopus database using the keywords alternative fuels, hydrogen and ammonia in relation to maritime transportation indicate that researchers from the United States, China, and the United Kingdom collectively contributed to approximately 50% of the total scientific publications. The findings of this study shed light on the current state of research on hydrogen and ammonia as alternative fuels in the context of maritime transportation, providing invaluable references and insights to guide future studies, with the IMO's net-zero carbon emission targets serving as a critical cornerstone for identifying key research directions.
Keywords: Hydrogen; Ammonia; Alternative fuels; IMO; Bibliometric analysis; ENGINE PERFORMANCE; DIESEL-ENGINE; EMISSIONS; FUEL; COMBUSTION; INJECTION; GAS; TECHNOLOGIES; CLIMATE; ENERGY; Environmental Sciences & Ecology